Removal of emerging organic pollutants from soil medium with engineered nanomaterials – Advances and future prospects - Mohammadreza Khalaj; Mohammadreza Kamali; Rahim Molaey; Tejraj M. Aminabhavi; Luísa Margarida Martins; M. Elisabete V. Costa; Isabel Capela; Raf Dewil (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Simplified hydrogen storage in nanocomposites optimized by artificial intelligence - Behrouz Nemati; Mohammadreza Kamali; Sara Zandi; Tejraj M. Aminabhavi; Raf Dewil; M. Elisabete V. Costa; Isabel Capela (Chemical Engineering Journal, 2025)

Mechanistic analysis of photocatalytic transformation of naphthalene using a nano-O-doped-g-C3N4-CuO n-p heterojunction - Mohammadreza Khalaj; Mohammadreza Kamali; Ana C. Estrada; Sh.Rasekh; Tito Trindade; Tejraj M. Aminabhavi; Nikolai A. Sobolev; M. Elisabete V. Costa; Raf Dewil; Isabel Capela (Process Safety and Environmental Protection, 2025)

Biohythane production via anaerobic digestion process: fundamentals, scale-up challenges, and techno-economic and environmental aspects - Seyedeh Azadeh Alavi-Borazjani; Luís António da Cruz Tarelho; Maria Isabel Capela (Environmental Science and Pollution Research, 2024)
Biohythane, a balanced mixture comprising bioH 2 (biohydrogen) and bioCH 4 (biomethane) produced through anaerobic digestion, is gaining recognition as a promising energy source for the future. This article provides a comprehensive overview of biohythane production, covering production mechanisms, microbial diversity, and process parameters. It also explores different feedstock options, bioreactor designs, and scalability challenges, along with techno-economic and environmental assessments. Additionally, the article discusses the integration of biohythane into waste management systems and examines future prospects for enhancing production efficiency and applicability. This review serves as a valuable resource for researchers, engineers, and policymakers interested in advancing biohythane production as a sustainable and renewable energy solution.

Sustainability insights into the synthesis of engineered nanomaterials - Problem formulation and considerations - Mohammadreza Khalaj; Mohammadreza Kamali; Tejraj M. Aminabhavi; M.Elisabete.V. Costa; Raf Dewil; Lise Appels; Isabel Capela (Environmental Research, 2023)

Chemobrain: mitoxantrone-induced oxidative stress, apoptotic and autophagic neuronal death in adult CD-1 mice - Ana Dias-Carvalho; Mariana Ferreira; Ana Reis-Mendes; Rita Ferreira; Maria Lourdes Bastos; Eduarda Fernandes; Susana Isabel Sá; João Paulo Capela; Félix Carvalho; Vera Marisa Costa (Archives of Toxicology, 2022)

Four decades of chemotherapy-induced cognitive dysfunction: comprehensive review of clinical, animal and in vitro studies, and insights of key initiating events - Ana Dias-Carvalho; Mariana Ferreira; Rita Ferreira; Maria de Lourdes Bastos; Susana Isabel Sá; João Paulo Capela; Félix Carvalho; Vera Marisa Costa (Archives of Toxicology, 2022)

Hydrolytic-Acidogenic Fermentation of Organic Solid Waste for Volatile Fatty Acids Production at Different Solids Concentrations and Alkalinity Addition - Tânia Gameiro; Maria Lopes; Rita Marinho; Pompilio Vergine; Helena Nadais; Isabel Capela (Water, Air, & Soil Pollution, 2016)

Optical Fiber Technology for Monitoring and Preventing Biomass Washout from Bioreactors: a Case Study with a Sequencing Batch Reactor (SBR) - Flávio C. Silva; Martinho A. S. Martins; Lúcia Bilro; Rogério N. Nogueira; Isabel Capela; J. Jacob Keizer (Water, Air, & Soil Pollution, 2015)

Olive Oil Mill Wastewater to Volatile Fatty Acids: Statistical Study of the Acidogenic Process - Tânia Gameiro; Fátima Sousa; Flávio C. Silva; Cátia Couras; Maria Lopes; Vitória Louros; Helena Nadais; Isabel Capela (Water, Air, & Soil Pollution, 2015)

Assessing foraging strategies of herbivores in Mediterranean oak woodlands: a review of key issues and selected methodologies - Maria Isabel Ferraz de Oliveira; Elsa Lamy; Miguel N. Bugalho; Margarida Vaz; Cristina Pinheiro; Manuel Cancela d’Abreu; Fernando Capela e Silva; Elvira Sales-Baptista (Agroforestry Systems, 2013)

Carbon storage in harvested wood products: implications of different methodological procedures and input data—a case study for Portugal - Ana Cláudia Dias; Luís Arroja; Isabel Capela (European Journal of Forest Research, 2012)

Life cycle assessment of printing and writing paper produced in Portugal - Ana Cláudia Dias; Luis Arroja; Isabel Capela (The International Journal of Life Cycle Assessment, 2007)

Life cycle assessment of printing and writing paper produced in Portugal - Ana Cláudia Dias; Luis Arroja; Isabel Capela (The International Journal of Life Cycle Assessment, 2007)